Multinationals' Policies and Local Responses: findings from cross-national case studies in Germany, France and the USA. (1st April 2008) - Pamela Meil
Abstract : This paper examines the complex interaction between globalisation practices of multinational corporations and the governing potential of response by local systems of employment regulation in light of rationalisation processes linked to financial market driven strategies. It investigates this issue by looking at optimisation programmes conceived and developed at the central headquarters of two German multinational companies and then traces their implementation at local sites in three different international settings: Germany, the USA and France. A central focus was the role that industrial relations systems play in the transformation process and whether (or how) the response varies according to the strength and coordination of the institutionalised system of industrial relations. The study shows that differences still remain in the form and strength of the industrial relations systems in these three countries. However, in all three cases, a new development in industrial relations is taking place in which areas potentially relevant for bargaining are left 'unoccupied'. That is, they are missed completely in the traditional negotiating agendas of industrial relations actors.